Estudio del complejo teniasis cisticercosis en dos áreas rurales de la parte alta de la provincia de El Oro. - Muñoz Lecaro, Manuel (2005)
The purpose of this investigation was to determine the prevalence of Teniasis and Cisticercosis in four rural communities of the high lands of El Oro province in Ecuador. We gathered 553 of blood serum and 514 fecal samples of population investigated.